Edward Lhwyd in Cornwall. (1st December 2019) - Roberts, Brynley
This article discusses Edward Lhwyd's visit to Cornwall in 1700, drawing on his correspondence to demonstrate the support he received from Cornish scholars and antiquarians, his itinerary and fieldwork methodology, his treatment of the Cornish language, and the manuscript materials available to him.